Training for health ministry: Design and implementation of library resources to incorporate health education and promotion into theological education - Fuller, Tyler J. (Teaching theology and religion, 2020)
This case study leverages existing library assets and curated educational resources for students, pastors, and health ministers by seeking to increase their understandings of how religion intersects with, and informs, health education and promotion, and public health more broadly, while equipping them with tools to engage in important conversations about health ministry. This article describes and evaluates a library-based research guide that is a replicable model for collaborative ministerial training about engaging, evaluating, and participating in health education and promotion, which is a vital component of theological education. Much of the pedagogical conversation around religion and health within theological and religious studies has focused on the ways that religion assists in the socio-cultural construction of health and healing. This case study expands on this conversation by detailing how seminary students, pastors, and health ministers can also use public health knowledge to better provide services to their congregations and communities. This model provides long-term, publicly-available, asynchronous access to these materials, making it a valuable resource for theology schools.